KINERJA ARUS KAS PERUSAHAAN SEKTOR TRANSPORTASI DALAM MASA PENGENDALIAN PANDEMI COVID-19 - Indra Satria; Cotoro Mukri; Achmad Djamil (FEB-UP Press, 2022)
Abstract Indonesia's transportation sector experienced the worst conditions during the Covid-19 pandemic in 2020. Along with the recovery of economic conditions through the Covid-19 pandemic control policy in 2021, this study was conducted to evaluate the performance of transportation sector companies during the Covid-19 pandemic control period. the. Performance appraisal is carried out according to the cash flow ratio analysis method. Purposive sampling method was determined in determining the selected companies for research. The results show that the cash flow performance of transportation sector companies has increased in terms of liquidity and solvency. On the other hand, the efficiency level has decreased. Keywords: Cash Flow Performance